Social oppression and American cultural imperialism: the crisis of the Muslim Minority Groups’ Identity in Terrorist by John Updike - Fakhrulddin, Saif Raed Nafia; Bahar, Ida Baizura (Australian International Academic Centre, 2022)
Terrorist (2006) by John Updike has been classified within the post-9/11 novel genre where many American authors depict their counter-narratives to the horrific event of 9/11. The novel revolves around the life of a young teenager named Ahmad and his religious mentor, Shaikh Rashid, who are accused as terrorists. This study problematises the issue of the identity of Muslim characters in facing oppression using the concept of cultural imperialism by Iris Marion Young (1990), focussing on the social treatment of Muslim minority characters in America perceived as inferior to the entire American cultural mainstream. The objective of this study then is to examine the author’s depictions of the American society as the cultural imperialism persecuting Muslim characters. The findings highlight the Muslim characters’ inability to emulate the prevailing American cultural imperialism which oppresses them. As such, the study’s originality lies in the interpretation of the aversive affinity between Muslim minority groups and American cultural imperialism from a social perspective. Thus, the social aspects of social oppression and the American cultural imperialism will be the core of the study’s novelty regarding the view of Muslims in America in the years ensuing the events of 9/11.